Differences between childhood- and adulthood-onset eosinophilic esophagitis: An analysis from the EoE connect registry. Issue 3 (March 2023) - Laserna-Mendieta, Emilio José; Navarro, Pilar; Casabona-Francés, Sergio; Savarino, Edoardo V; Pérez-Martínez, Isabel; Guagnozzi, Danila; Barrio, Jesús; Perello, Antonia; Guardiola-Arévalo, Antonio; Betoré-Glaria, María Elena; Blas-Jhon, Leonardo; Racca, Francesca; et al.
Abstract: Background: Direct comparisons of childhood- and adulthood-onset eosinophilic esophagitis (EoE) are scarce. Aim: To compare disease characteristics, endoscopic and histological features, allergic concomitances and therapeutic choices across ages. Methods: Cross-sectional analysis of the EoE CONNECT registry. Results: The adulthood-onset cohort (those diagnosed at ≥18y) comprised 1044 patients and the childhood‐onset cohort (patients diagnosed at <18 y), 254. Vomiting, nausea, chest and abdominal pain, weight loss, slow eating and food aversion were significantly more frequent in children; dysphagia, food bolus impaction and heartburn predominated in adults. A family history of EoE was present in 16% of pediatric and 8.2% of adult patients ( p <0.001). Concomitant atopic diseases did not vary across ages. Median±IQR diagnostic delay (years) from symptom onset was higher in adults (2.7 ± 6.1) than in children (1 ± 2.1; p <0.001). Esophageal strictures and rings predominated in adults ( p <0.001), who underwent esophageal dilation more commonly ( p = 0.011). Inflammatory EoE phenotypes were more common in children ( p = 0.001), who also presented higher eosinophil counts in biopsies ( p = 0.015) and EREFS scores ( p = 0.017). Despite PPI predominating as initial therapy in all cohorts, dietary therapy and swallowed topical corticosteroids were more frequently prescribed in children ( p <0.001). Conclusions: Childhood‐onset EoE has differential characteristics compared with adulthood-onset, but similar response to treatment.